Wild mushrooms Clitocybe alexandri and Lepista inversa: In vitro antioxidant activity and growth inhibition of human tumour cell lines - Vaz, Josiana A. (2010)
The in vitro antioxidant and growth inhibitory activity of extracts obtained from two Portuguese wild mushrooms (Clitocybe alexandri and Lepista inversa) was studied in human tumour cell lines. The extracts were phenolic (methanolic and ethanolic) and polysaccharidic (boiling water). The antioxidant activity assays included evaluation of radical-scavenging capacity, reducing power and inhibition of lipid peroxidation measured in liposome solutions. Extract-induced cell growth inhibition was measured in four different tumour cell lines (lung, breast, colon and gastric cancer) using the SRB assay. The polysaccharidic extract oft. inversa was the most potent as antioxidant (EC50 < 1.8 +/- 0.1 mg/ml), while the phenolic ethanolic extract of C alexandri was the most potent as inhibitor of growth of the studied cancer cell lines (Gl(50) <26.0 +/- 1.3 mu g/ml). Together, these activities indicate that these mushrooms are promising sources of bioactive compounds. (C) 2010 Elsevier Ltd. All rights reserved.